Advances in bioinformatics and computational biology : second Brazilian Symposium on Bioinformatics, BSB 2007, Angra dos Reis, Brazil, August 29-31, 2007 proceedings - Brazilian Symposium on Bioinformatics (2nd : 2007 : Angra dos Reis, Brazil); Sagot, Marie-France, 1956-; Walter, Maria Emilia M. T. (Marie Emilia Machado Telles) (Berlin : Springer-Verlag, 2007)
42